LITHOLOGICAL-FACIES ZONALITY OF LOWER CRETACEOUS DEPOSITS OF THE KASHKADARYA TROUGH - Juraev , Fazliddin Ochilkhanovich (Digital technologies in industry, 2025)
Lower Cretaceous deposits are very widespread in the study area, and their sediments, due to their specific lithological-facial and paleontological features, are clearly and vividly distinguished in the section of the entire Mesozoic sedimentary complex. A comprehensive study of the material composition of Lower Cretaceous rocks, facies-paleogeographic conditions of accumulation of various lithological layers and the establishment of a close genetic relationship between facies types of rocks, as well as patterns of distribution of various minerals according to geological-paleogeographic patterns are important search criteria in geological exploration.